Faktor-Faktor Yang Berhubungan Dengan Imunisasi Dasar Tidak Lengkap Di Puskesmas Sidomulyo Kota Pekanbaru - Cindy Alesia Cindy Alesia; Buchari Lapau; Yessy Harnani; Yuyun Priwahyuni; Miklon Miklon (Jurnal Kesehatan Komunitas, 2021)
Complete basic immunization occurs if certain vaccines are given to babies; if one dose or more certain vaccines are not given, incomplete basic immunization occurs. The objective of the study is to detect the management of basic immunization, and factors affecting incomplete basic immunization at the Sidomulyo health center in Pekanbaru in 2020. This research was a mixed methodology in which one Qualitative research design confirms 3 informants namely the health center head, immunization section head, and immunization worker. The researcher conducted a deep interview, observation, and reviewing documents. Data analysis was conducted by data reduction, conclusion, and presentation. This used a quantitative case-control study design, the researcher found a population of 286 cases, and a population of 1,308 controls. Each of 205 cases and 205 controls were taken from its population by systematic random sampling. The researcher collected data through interviews using a questionnaire containing close-ended questions and analyzed data by univariate, bivariate, and logistic regression analysis. Qualitative research design found planning and implementation were running well, but monitoring has not been conducted. The case-control study found a causal relationship with each of intellectual development (CI 95%, OR=3.5-10.4), attitude (CI 95%, OR =3.6-8.5), family-supporting (CI 95%, OR= 2.3-8.5), and side effect (CI 95%, OR =1.9-4.4) and basic immunization. It concludes the management of health centers should monitor basic immunization,Â  and enhance health promotion on intervention concerning intellectual development, positive attitude, family-supporting, and side effect of vaccines to complete basic immunization. Each intervention developed to be suggestions.